FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PEMANEN KELAPA SAWIT PADA PT. KASWARI UNGGUL DI DESA RANTAU KARYA KECAMATAN GERAGAI KABUPATEN TANJUNG JABUNG TIMUR - Asmaida Asmaida; Ramos Manik (Universitas Batangahari Jambi, 2021)
The study aims to get an idea of the productivity of palm harvesting workers at PT.Kaswari Unggul in Rantau Karya Village Geragai District Tanjung Jabung Timur Regency, Which describes the age, number of family dependents, tenure, mileage, wages and premiums in PT.Kaswari Unggul and how these factors affect the productivity of palm harvesting workers. The analysis method used was a descriptive analysis method by distributing questionnaire in the field, while secondary data was obtained from companies associated with research activitiesTo test the influence of factors affecting productivity in harvesting work using linear regression analysis methods, Then the method is carried out which includes hypothesis testing, f test, t test, coefficient of determination analysis (R2) and to analyze data using SPSS statistics 20. Software the total sample in the study were 33 harvesters. Based on the results of the research obtained it can be concluded that the productivity of harvesters on average per month is 1.010,33 kg. Significant factors affecting harvester productivity are premium factors (x6), while the factors that do not significantly affect harvester productivity are age (x1) number of family dependents (x2),tenure (x3), mileage (x4), wages (x5)Keywords: productivity, harvesting workers, palm